Amelioration of Cognitive Deficit by Moringa oleifera flower extract in a Scopolamine-Induced Alzheimer’s Disease-Like Condition in a Rat Model (Asian Journal of Pharmaceutics (AJP), 2025)
Alzheimer’s disease (AD) is the most prevalent form of dementia, marked by cognitive decline,amyloid-β (Aβ) accumulation, cholinergic dysfunction, neuroinflammation, and oxidative stress. Moringa oleiferaflower (MOF) extract, rich in flavonoids, phenolics, vitamins, and calcium, has been traditionally recognized forits medicinal properties. This study explored the neuroprotective potential of MOF extract against scopolamine(SCO)-induced dementia in rats. Materials and Methods: Thirty Wistar rats were divided into five groups:Control (normal saline), SCO (3 mg/kg, i.p., days 15–21), MOF 200 + SCO, MOF 400 + SCO (administered orallyfor 21 days), and Donepezil (5 mg/kg, i.p., 21 days). Cognitive performance was assessed using the Morris watermaze and Y-maze tests. On day 21, rat brains were collected for biochemical estimations (Aβ), acetylcholinesterase(AChE), nuclear factor erythroid 2-related factor 2 (Nrf-2), superoxide dismutase (SOD), reduced glutathione(GSH), and malondialdehyde (MDA), and histopathological analysis. Results: SCO administration significantlyimpaired memory, increased Aβ and AChE activity, suppressed Nrf-2 expression, and altered antioxidant defenseby reducing GSH and SOD while elevating MDA levels. Pretreatment with MOF extract markedly improvedcognitive performance, reduced Aβ and AChE activity, restored Nrf-2 expression, and normalized oxidative stressmarkers. Histopathological findings supported these protective effects. Conclusion: MOF extract effectivelyameliorated SCO-induced cognitive impairments and oxidative damage, demonstrating its potential as a naturalneuroprotective agent for the management of AD.